Analisis Kinerja Keuangan Bank Aladin Syariah - Ambas Hamida; Kulkarni Kulkarni (IAIN Palopo, 2021)
Islamic banking sector is currently facing serious challenges. Because the whole world is facing the COVID-19 pandemic. In the midst of a pandemic, Islamic banking has enough challenges. One of the negative impacts of the pandemic is the performance of companies in the financial sector. Financial performance research can be determined by financial and non-financial variables. This study only focuses on analyzing the bank's financial performance with three variables, namely ROA, CAR, and BOPO. This study aims to determine the financial performance of Aladin Syariah Bank in the 2020-2021 period. Using quantitative research methods using secondary data, namely the annual financial statements. The population of this research is all published financial reports, with samples of financial statements for the period 2020-2021, as well as data collection techniques with documentary studies. The results of this study indicate that the financial performance of Aladin Syariah Bank for the period 2020-2021 shows good performance in terms of financial ratios CAR, and BOPO because they are in accordance with Bank Indonesia standards. While the ROA ratio does not show good performance.Because it is not in accordance with Bank Indonesia.